2018
DOI: 10.1111/cdoe.12377
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of the validity of patient satisfaction questionnaires pertaining to oral health care

Abstract: The extent of validity and reliability of the included instruments was largely unassessed, and appropriate instruments for populations outside of those belonging to general adult populations were not present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
1
27
0
3
Order By: Relevance
“…However, satisfaction appears differently from the previous multiple factors in DSQ 13 for the reduced number of items in DCS. Nevertheless, a critical review of satisfaction questionnaires suggests that most satisfaction instruments with adequate internal consistency can be considered to be unidimensional 31 . For a comprehensive understanding of DPR, these two unidimensional constructs can function as reciprocal complements justified by the divided factor structure beyond the conceptual differences proposed 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, satisfaction appears differently from the previous multiple factors in DSQ 13 for the reduced number of items in DCS. Nevertheless, a critical review of satisfaction questionnaires suggests that most satisfaction instruments with adequate internal consistency can be considered to be unidimensional 31 . For a comprehensive understanding of DPR, these two unidimensional constructs can function as reciprocal complements justified by the divided factor structure beyond the conceptual differences proposed 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, a sub‐optimal number of items for each dimension (model 1 in Figure ) might have restrained the model fit of conceptual design in the factor structure (three or more items recommended for a solid factor) 38 . Besides, dimensions analysed in the study were inherently limited to those in the established scales with a possible chance of missing important traits such as empathy 11 and responsiveness 11,31 . Those limitations aside, this study investigated structural validity of both constructs thoroughly and rigorously from the initial exploration to the confirmation of factor solution.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study assessed the difference in dental satisfaction with the Dental Satisfaction Index, and the findings were similar to those reported in the current study, with similar values for the overall index and the 2 subscales (Cost and Access), favoring public service provision through school dental services (Brennan et al 2001). Although the overall construct measured by the COPAS and Dental Satisfaction Index is similar, the theoretical basis for scale construction and the items are different (Nair et al 2018). This previous study (Brennan et al 2001) was conducted in 1 state in Australia (South Australia), and the current study comprised a national sample.…”
Section: Discussionmentioning
confidence: 99%
“…Since health care systems aim to meet the health care needs of people under their care, the evaluation of the differences between private and public care facilities needs a measurement from the perspective of the very individuals who are under the purview of these health care systems. Quality of care measured from the perspective of the patients or their caregivers would be appropriate for such a measurement (Nair et al 2018). This is especially important because health care providers often act as an agent to help make a choice for individuals who are seeking care (Donabedian 1971), and their ability to act as adequate proxies is unassessed.…”
Section: Introductionmentioning
confidence: 99%
“…A current critical review identified several instruments that measure dental satisfaction for overall oral care provision rather than those for specific treatments or subgroups within the overall oral care provision . These instruments measure the performance of care using multi‐item questionnaires, as the multidimensionality of the concept of oral care satisfaction requires.…”
Section: Introductionmentioning
confidence: 99%